PENGARUH EKSTRAK KULIT MANGGIS (Garcinia Mangostana L) TERHADAP KADAR FLAVONOID DAN KUALITAS ORGANOLEPTIK NATA DE SOYA - Kalkoy, Yosualda; Pattipeilohy, Mery; Sangur, Kristin; Mahulette, Ferymon (Program Studi Pendidikan Biologi FKIP Unpatti, 2025)
Background: Mangosteen (Garcinia mangostana L) is one of Indonesia's tropical fruits. Mangosteen peel extract can be used as a natural colorant for a variety of products such as medicines, cosmetics, beverages and processed foods. Mangosteen peel contains compounds of flavonoids, saponins, tannins, steroids/triterpenoids. Anthocyanins in mangosteen skin can be used as a natural colorant for processed food products nata de soya made from tofu liquid waste. Research Methods: This research was conducted on April 17 - August 21, 2023 at the Basic Chemistry Laboratory of FMIPA and Biology Laboratory of FETT. This type of research is quantitative experimental research, arranged in a completely randomized design. With four treatments of flavonoid levels of 10, 20, 30, 40% mangosteen peel extract and one control. Results: The results showed that there was an effect of mangosteen peel extract as a natural colorant on the flavonoid content of nata de soya. Conclusion: The Smallest Real Difference Test (BNT) at the significance level α 0.05 and the significance level α 0.01 and the results of the BNT Test at the 0.05% level and the 0.01% level for each indicator show that the provision of mangosteen peel extract to the flavonoid content of nata de soya, gives very different results.